2013
DOI: 10.1152/japplphysiol.00636.2013
|View full text |Cite
|
Sign up to set email alerts
|

Heat stroke activates a stress-induced cytokine response in skeletal muscle

Abstract: Heat stroke (HS) induces a rapid elevation in a number of circulating cytokines. This is often attributed to the stimulatory effects of endotoxin, released from damaged intestine, on immune cells. However, parenchymal cells also produce cytokines, and skeletal muscle, comprising a large proportion of body mass, is thought to participate. We tested the hypothesis that skeletal muscle exhibits a cytokine response to HS that parallels the systemic response in conscious mice heated to a core temperature of 42.4°C … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 66 publications
(70 citation statements)
references
References 73 publications
(111 reference statements)
4
66
0
Order By: Relevance
“…1999; Welc et al. 2013a). In a heat stroke model, 1 h of hyperthermic exposure was sufficient to induce activation in SAPK signaling in skeletal muscle (Welc et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1999; Welc et al. 2013a). In a heat stroke model, 1 h of hyperthermic exposure was sufficient to induce activation in SAPK signaling in skeletal muscle (Welc et al.…”
Section: Discussionmentioning
confidence: 99%
“…1999) and 30 min (Welc et al. 2013a) of hyperthermia. In our current study, we found evidence supporting activated AP‐1 signaling as relative protein abundance of AP‐1 was increased in nuclear fractions following 4 and 6 h of heat stress compared to thermoneutral.…”
Section: Discussionmentioning
confidence: 99%
“…; Welc et al . ). IL‐6 has been found to have many different functions that fall under categories of both pro‐ and anti‐inflammatory activity, wound healing, cell survival signalling and metabolic control, and has been shown to have a number of functional roles in acute and chronic illnesses.…”
Section: Introductionmentioning
confidence: 97%
“…Plasma TNF␣ was undetectable at the end of heat exposure in both vehicle-and infliximab-treated rats, and the antibody had no effect on maximum T c (T c,Max ϭ 43.0°C) or other heat stroke responses. We showed in mice that plasma TNF␣ was either unchanged or decreased at T c,Max and later time points of heat stroke recovery (7,15,30), yet robust increases in sTNFRI and II were observed throughout recovery (2). Plasma sTNFRs have been shown to protect against TNF␣-induced cytokine production and cytotoxicity (29), which is congruent with the purported protective actions of the soluble receptors in heat stroke patients (10).…”
mentioning
confidence: 99%